PROFITABILITY RATIO ANALYSIS AT PKU MUHAMMADIYAH BANTUL HOSPITAL - Monica, Mega; Safitri, Teti Anggita (PT. Antis International Publisher, 2025)
Objective: The focus of this research is the profitability ratio at PKU Muhammadiyah Bantul Hospital in 2021–2023. Method: This research was conducted quantitative descriptively using financial ratio analysis. The data used comes from company financial reports taken from PKU Muhammadiyah Bantul Hospital. Results: The research results show that the profitability ratio, which consists of NPM (Net Profit Margin) fell from 0.1097 to 0.0691, ROE (Return On Equity) fell from 0.2140 to 0.0875, and ROA (Return On Assets) fell from 0.2835 to 0.0878. This decline shows that the company's performance declined during that period. Novelty: This condition is caused by various factors, including changes in demand patterns for health services, or increases in operational costs that are not offset by equivalent revenue growth.